Exploring alternative practices in urban water management through the lens of circular economy–A case study in the Barcelona metropolitan area. (20th December 2021) - Ramírez-Agudelo, Nancy Andrea; de Pablo, Joan; Roca, Elisabet
Abstract: Urban water management has recently been questioned because of the fragmented nature of the urban water system and its linear model. The integration and management of water systems are currently recognized as a socio-technical challenge that must be addressed for a more sustainable urban water management. In the short term, a key factor for its transition will be integration of alternative practices that allow for experimentation, learning, and scaling up. This study aims to identify potential shifts supported by two alternative practices for water reuse: nature-based solutions and water reuse technologies, using circular economy principles as analytical categories. The research uses a case study, the Besòs river of the Barcelona metropolitan area, to show that: i) improving biodiversity and water quality helps to regenerate natural capital; ii) water reuse for streamflow augmentation keeps resources in use and promotes synergies, which benefits social livability; and iii) risk management and a potential fit-to-purpose strategy can marginally help to avoid waste externalities. This research has shown that the CE principles are applicable as a framework for identifying the interconnected shifts promoted by water systems. A reflexive understanding of the alternative practices provides deeper insight into the experiences, barriers, and shifts that allow innovative interactions in specific urban contexts and can deliver additional benefits for society. This knowledge can be useful for integrated urban management; however, further integration of cross-sectoral collaboration and flexibility are required. Highlights: Water systems integration and management is a long-term socio-technical challenge. Alternative practices support in complementary ways the Circular Economy principles. Local alternative practices contribute towards sustainable urban water management. Cross-sectoral collaboration and flexibility are key for shifts in the urban water systems.